An Error Analysis of Students with Differences in Learning Outcomes in Solving Story Problems Based on the Newman Procedure - Fury Styo Siskawati (Universitas Islam Jember, 2017)
The purpose of this research are to describe the location of student error with high value in completing the story problem based on Newman procedures, describing the location of student error with middle value in completing the story problem based on Newman procedures, and describe the location of student error with low value in completing the story problem based on Newman procedures. The kind of this research is descriptive research with qualitative approach. The subjects of this research are 3 students with different values. The data collection methods used is test, interview and documentation, where to test the data credibility using triangulation time and method. The result of the research are student with high value making error on process skill and write the end of answer. The student with middle value making error on doing transformation, process skill and write the end of answer. The student with low value making error on understanding the problem, doing transformation, process skill and write the end of answerKey words: problem solving error, story problem, and Newman procedure